Unravelling the strands of 'patriarchy' in rural innovation: A study of female innovators and their contribution to rural Connemara. (August 2017) - Ní Fhlatharta, Aoife M.; Farrell, Maura
Abstract: While studies of rural women and their participation in the innovation milieu continues to be championed, within the Republic of Ireland very few studies have been conducted on Irish women's participation and value in this sector, with much of the limited research being curtailed to the realm of Irish agriculture. Addressing the paucity of studies, this paper specifically explores the pioneering role of women in rural innovation in areas located along the west coast region of Ireland, to uncover the connection between these women's enterprises and the overall development of the Irish hinterlands. The paper is based on both qualitative and quantitative research with 54 female innovators, who shared their experiences and difficulties as an innovator in a peripheral region. As the work of rural women often goes unnoticed and unrecorded, this research employed a feminist perspective to gain a deeper understanding of the role of women in rural innovation. The findings of the research highlight the dual role of rural women as innovators; furthermore show female innovators as being of paramount importance for the overall development of Europe's rural regions. Despite their imperativeness as agents of positive change; offering as they do an alternative path to sustainable development for the Western regions, the women were unable to appreciate their significance due to patriarchal and hegemonic ideologies which still impact women residing in rural areas. Highlights: Explores the pioneering role of women in rural innovation. Rural restructuring is furnishing rural women with new employment trajectories. Rural women engaged in the SME sector prove instrumental in rejuvenating rural regions. Hegemonic masculine constructs ingrained within the rural idyll are prohibiting women from realizing their focal role in SMEs.